1975
DOI: 10.1111/j.1469-8137.1975.tb01338.x
|View full text |Cite
|
Sign up to set email alerts
|

Electron Microscopical Studies of the Microflora of Roots of Sand Dune Grasses

Abstract: SUMMARYScanning and transmission electron microscopy were used to study microfiora of roots of three species of sand dune grasses. Observations were made on the mucigel on intact epidermal cells and the colonization of sloughing superficial root cells by bacteria and actinomycetes. Thin sections of the same root samples showed that bacteria penetrated epidermal cells either by perforating the cell wall or by exploiting the middle lamella between adjacent cells as an avenue of entry. Cortical cells of all three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
1

Year Published

1978
1978
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(25 citation statements)
references
References 27 publications
2
22
1
Order By: Relevance
“…As often with root-colonizing bacteria (Foster & Rovira, 1973;Old & Nicolson, 1975;Bowen, 1979;Campbell et al, 1987), cells of CHA0 were found preferentially at the junction of epidermal cells (Fig. 4), a microhabitat with enhanced exudation, humidity and mucigel (Bowen & Rovira, 1976).…”
Section: Discussionmentioning
confidence: 95%
“…As often with root-colonizing bacteria (Foster & Rovira, 1973;Old & Nicolson, 1975;Bowen, 1979;Campbell et al, 1987), cells of CHA0 were found preferentially at the junction of epidermal cells (Fig. 4), a microhabitat with enhanced exudation, humidity and mucigel (Bowen & Rovira, 1976).…”
Section: Discussionmentioning
confidence: 95%
“…However, the longevity of cortical cells has important implications in determining the potential resistance of the cortex to a number of diseases (Yeates and Parker 1985). RCS is typically followed by the growth of fungi and bacteria in living and dead root tissues (Old and Nicolson 1975). After RCS, the root cortex has reduced capacity for defense including the formation of lignotubers or cell wall thickening in response to fungal hyphae (Holden 1976).…”
Section: Regulation Of Rcs Developmentmentioning
confidence: 99%
“…These intercellular spaces were filled with mucigel and seemed to be rich in nutrients for bacteria. Most investigators have reported that microorganisms in the plant rhizoplane are distributed in the basal part of the root, ruptured sites, cell junctions, lateral roots or root hairs, but not in the root apex (2)(3)(4)(5)(6)(7)(8)(9)(10)(12)(13)(14)(15). Although we could not compare directly the distribution of the N 2 -fixing bacteria in the basal part and root tip region of rice root in this experiment, we consider that the root tip region is favorable for microorganism multiplication since young epidermal and root cap cells may secrete exudates, in addition to the debris of the sloughed-off root cap cells.…”
Section: Resultsmentioning
confidence: 99%
“…Both transmission (TEM) and scanning electron microscopy (SEM) have been applied to the investigation of rhizosphere microorganisms by several researchers (2)(3)(4)(5)(6)(8)(9)(10)(11)(12)(13)(14)(15). However, only a few ultrastructural studies of associative N 2 -fixing bacteria with plant roots have been reported.…”
mentioning
confidence: 99%